Construyendo una cultura de innovación. Una propuesta de transformación cultural (2015)
This paper presents the cultural transformation model for innovation that has been implemented in the Sumicol Company, which is part of the Corona Organization. The model distinguishes three stages: current culture diagnosis, target culture definition, and identification of the gaps that must be filled in order to reach that culture. The research was carried out as a case study focusing on the qualitative perspective made from documentary analysis, in-depth interviews and focus groups, and supplemented with a quantitative description of culture. From the results a cultural transformation model, the identification of former culture, and the identification of cultural traits for business innovation, were obtained.